Od cytatu do plagiatu – eksploracje infoetyczne (cz. 1) [From the citation to the plagiarism – infoethical explorations (vol. 1)] - Wyrostkiewicz, Michał (Biuletyn Edukacji Medialnej [Media Education Bulletin], 2016)
The road from the citation to the plagiarism is very short. It is easy to enter this path. This is because scientific research is “high risk area of plagiarism” This is due to the fact that meaningful research demanding the use of the publications of other authors. This use must be done with a respect of other authors and recipients prepared publication. Otherwise, social progress and integral development the researcher and other persons are in grave danger. Plagiarism is not a problem with the relationship between the researcher and publications, but between the scientist‑plagiarist and the others. Plagiarism is a negation of moral goodness, justice, solidarity and the common good.
https://katalog.adlr.link/Record/ai-53-479354